2022
DOI: 10.1002/bse.3293
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental, social and governance score on operating performance after mergers and acquisitions

Abstract: This paper examines how the corporate social responsibility performance of the acquirer firm, measured with the environmental, social and governance score, is related to postmerger operating performance, by analysing 796 merger operations that took place between 2011 and 2018. The analysis was carried out by first considering the full sample and then dividing the sample into three subsamples: acquirer companies with an environmental, social and governance score below the median, acquirer companies with a ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…A study of 796 transactions taking place between 2011 and 2018 found that acquirers with a high ESG rating (above the median Refinitiv ESG score) achieved a significant improvement in postdeal operating performance, whereas this was not the case for acquirers with a low rating (below the median Refinitiv ESG score). [13] Another study, examining 1,556 US mergers from 1992 to 2007, found that deals completed by acquirers with high ESG scores took less time to complete, improved post-deal operating performance, and increased the long-term stock returns of these acquirers versus those with low ESG scores. [14] Risks of ignoring ESG in M&A…”
Section: Performance Benefitsmentioning
confidence: 99%
“…A study of 796 transactions taking place between 2011 and 2018 found that acquirers with a high ESG rating (above the median Refinitiv ESG score) achieved a significant improvement in postdeal operating performance, whereas this was not the case for acquirers with a low rating (below the median Refinitiv ESG score). [13] Another study, examining 1,556 US mergers from 1992 to 2007, found that deals completed by acquirers with high ESG scores took less time to complete, improved post-deal operating performance, and increased the long-term stock returns of these acquirers versus those with low ESG scores. [14] Risks of ignoring ESG in M&A…”
Section: Performance Benefitsmentioning
confidence: 99%
“…Enterprise ESG performance is closely linked to their sustainable development and competitiveness. Technology M&As, by introducing advanced environmental technologies, social responsibility practices, and effective corporate governance mechanisms, can enhance an enterprise's ESG performance [55]. Such improvements in ESG performance help to boost the company's image among investors and consumers, consequently increasing their market value.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Further evidence emerged considering a specific event during a company's lifetime: an M&A operation. Teti and Spiga (2022) analysed how the CSP performance of the acquirer firm, measured with the ESG rating, is related to postmerger operating performance; they found a sort of U‐shaped relationship because, in the case of acquirers with very high ESG ratings, these companies might have to bear higher costs during integration with the target, hence reducing the value created by the operation.…”
Section: Thematic and Content Analysismentioning
confidence: 99%